Clinical value of optical coherence tomography in the early diagnosis of cervical cancer and precancerous lesions: a cross-sectional study - Cui, Xiaoli; Yang, Di; Zhang, Jing; Zhao, Yuqian; Cui, Zhumei; Wang, Chunyan; Qiao, Youlin (Frontiers in Oncology, 2024)
Background: This study aimed to measure the accuracy of optical coherence tomography (OCT) in the early diagnosis of high-grade cervical lesions and assess its diagnostic value in the triage of high-risk HPV infection.Method: From Jan 2019 to Jan 2021, women who visited the gynecology clinics of 2 hospitals for colposcopy were invited to participate in this study.Women aged 35 to 64 years old who were sexually active and had an intact cervix with a diameter of more than or equal to 2 cm were included in this study. Additionally, individuals with abnormal cytology, positive HPV test results, or other clinically suspicious symptoms or signs were referred. All participants were examined before colposcopy using OCT. Biopsy and/or ECC were conducted under colposcopy. We used the results of histopathology as the gold standard and assessed the accuracy of OCT.Results: Overall, 883 women were included in the analysis. Approximately 13.25% of women were ASCUS+ in cytological assessments, and 22.31% were positive for high-risk HPV. Nearly 15.18% of women were positive in OCT. Of them, 27 women were diagnosed with CIN2, and 33 were diagnosed with CIN3+ lesions. Among HPV-positive women, the detection rates for CIN2+ and CIN3+ were much lower for those who were negative in OCT, compared with NILM cytology (CIN2+: 20.0% vs. 30.0%, P=0.002, and CIN3+: 18.2% vs.27.3%, P=0.013). Among women who were positive for HPV16/18, the detection rate for CIN2+ was much lower for negative OCT, compared with NILM cytology (8.3% vs.15.0%, P=0.005). Compared to HPV and cytological tests, HPV combined with OCT had higher specificity for detecting CIN2+ and CIN3+ (96.1% vs. 93.2%, P=0.002; 93.8% vs. 91.3%, P=0.013). OCT triage after HPV genotyping had the highest AUC for detecting CIN2+ and CIN3+ cases among patients with high-risk HPV infection (0.921, 0.920).OCT is an accurate test for the early diagnosis of high-grade cervical lesions and has great diagnostic value in the triage of patients with high-risk HPV infection.